Protection of particular endonuclease R. Hind III cleavage sites by distamycin A, propyl-distamycin and netropsin. - Nosikov, V V (1977)
It is shown that three related antibiotics, distamycin A, propyl-distamycin and netropsin, can protect certain endo R.Hind III cleavage sites from attack by endonuclease, giving rise, after endo R.Hind III digestion, to larger DNA fragments. Bacteriophage lambda DNA has six recognition sites for Hind III enzyme. Three of these sites: shind III 2, 3 and 6 can be protected from nuclease action by all the antibiotics used. Propyl-distamycin protects partly shind III 5, too. Netropsin protects partly sites shind III 5 and 4, while distamycin A protects all the sites but shind III 1 so the Hind III digestion produces only two large fragments of lambda DNA.